Design and Implementation of Fault Diagnosis and Data Synchronization Scheme Based on Train Redundant Display Platform - TIAN Deqiang; JIANG Xuezhai; ZHANG Xiaofeng; ZHANG Guangqiang; LIAO Jifang (Kongzhi Yu Xinxi Jishu)
The display platform of train provides the train driver with the key data of the running train and receives control command input. Its operation reliability is very important for safe driving. In order to quickly locate and response to the fault of the display platform and reduce the impact of the fault on train operation, the paper proposes a scheme for real-time diagnosis and data synchronization of train display platform operation status based on redundant display platform with two display units. Firstly, the self-diagnosis of the display unit was realized to monitor and diagnose the equipment status in real time based on the application layer, and to quickly locate the problems such as application exit, system crash and anomalies in resource utilization. Secondly, based on the RS422 communication link, a reliable communication protocol was defined to achieve the mutual diagnosis and data synchronization of operation status between multiple display units, and solve the problems of self-diagnosis failure in abnormal state of the unit and failure to obtain key data of faulty unit. A function verification experiment was carried out based on the train redundant display platform to verify the effectiveness of this scheme. The experimental results indicate that on the one hand, this scheme provides comprehensive self-diagnosis and redundant display unit state mutual diagnosis from the application layer, providing a basis for fault analysis and localization. On the other hand, it provides a way for two display units to work coordinately through key data synchronization and storage functions.